2011
DOI: 10.1007/s10773-011-0739-5
|View full text |Cite
|
Sign up to set email alerts
|

Brief History of a Relativistic Century

Abstract: More than one century is passed by the publication of special relativity and few less by the birth of general relativity. Despite the great experimental successes of these theories, the study of the universe, is plagued by numerous unsolved problems. For example one of the most problems in cosmology is the cosmological constant, which governs the expansion of the universe, also known as dark energy. A substantial portion, about 60%, of the mass-energy in the universe is in a form of mysterious energy that is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…George Berkeley in his De Motu and later Mach proposed a deep criticism of Newton's thought [1]. In particular Mach concluded that the inertia would be an interaction that requires other bodies to manifest itself and it has no sense in a Universe consisting of only one mass [2]. Therefore the concept of absolute motion should be substituted with a totally relative motion.…”
Section: Introductionmentioning
confidence: 99%
“…George Berkeley in his De Motu and later Mach proposed a deep criticism of Newton's thought [1]. In particular Mach concluded that the inertia would be an interaction that requires other bodies to manifest itself and it has no sense in a Universe consisting of only one mass [2]. Therefore the concept of absolute motion should be substituted with a totally relative motion.…”
Section: Introductionmentioning
confidence: 99%